2010
DOI: 10.1007/s10895-010-0641-1
|View full text |Cite
|
Sign up to set email alerts
|

Intense White Luminescence from Combustion Synthesized Ca12Al14O33: Yb3+/Yb2+ Single Phase Phosphor

Abstract: The Ca(12)Al(14)O(33):Yb(3+)/Yb(2+) single phase nano-phosphor has been synthesized through combustion route and its luminescence and lifetime studies have been carried out up to 20 K using 976 and 266 nm excitations. The samples heated in open atmosphere have shown the presence of Yb in Yb(3+) and Yb(2+) states. The 976 nm excitation results a cooperative upconversion emission at 486 nm due to the Yb(3+) state and a broad band in the blue region and has been assigned to arise from the defect centers. The 266 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…The waveform within 400 nm-600 nm is the same as that reported in Ref. [6]. Xu et al [4] have suggested that the blue emission band of 486 nm can result from the cooperative process corresponding to the simultaneous radiation relaxation of a pair of excited Yb 3+ ions.…”
Section: Emission Spectrum Under Diode-laser Excitationsupporting
confidence: 82%
See 1 more Smart Citation
“…The waveform within 400 nm-600 nm is the same as that reported in Ref. [6]. Xu et al [4] have suggested that the blue emission band of 486 nm can result from the cooperative process corresponding to the simultaneous radiation relaxation of a pair of excited Yb 3+ ions.…”
Section: Emission Spectrum Under Diode-laser Excitationsupporting
confidence: 82%
“…[4] Investigations into Yb 3+ -doped materials have revealed that Yb 3+ ions can produce not only laser emission in the near infrared region from 900 nm to 1200 nm but also narrow and bright visible emission around 486 nm due to cooperative upconversion emission. [5,6] Cooperative upconversion luminescence is a special type of upconversion luminescence. [7] In the Yb 3+ system, two interacting ions in the excited state can emit one photon when they return to the ground state simultaneously, while the energy of the output photon is twice the energy of the single ion transition.…”
Section: Introductionmentioning
confidence: 99%
“…2 shows. 17,19 The two different [AlO 4 ], Al(1) and Al (2), in the ratio of 4 : 3, which are connected by a common corner and forms boat-shaped eight-member rings. The Al(1) atom is surrounded to one O(2) atom and three O(1) atoms.…”
Section: Phase Identification and Crystal Structurementioning
confidence: 99%
“…An interesting feature of Yb 3+ ion is that though no band is usually seen at 488 nm in its absorption spectrum, an emission at this wavelength is seen with appreciable intensity. This has been explained as due to cooperative emission [19,20]. Though, the process responsible for this emission is not very well understood it has been invoked in many upconversion studies [21].…”
Section: Introductionmentioning
confidence: 99%